2013
DOI: 10.1175/jcli-d-12-00446.1
|View full text |Cite
|
Sign up to set email alerts
|

Antarctic Low-Tropospheric Humidity Inversions: 10-Yr Climatology

Abstract: Humidity inversions are nearly permanently present in the coastal Antarctic atmosphere. This is shown based on an investigation of statistical characteristics of humidity inversions at 11 Antarctic coastal stations using radiosonde data from the Integrated Global Radiosonde Archive (IGRA) from 2000 to 2009. The humidity inversion occurrence was highest in winter and spring, and high atmospheric pressure and cloud-free conditions generally increased the occurrence. A typical humidity inversion was less than 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
85
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(95 citation statements)
references
References 37 publications
9
85
1
Order By: Relevance
“…Devasthale et al (2011) found a clear nonlinear relationship between humidity and temperature inversion strength in all seasons except during summer in the Arctic. Similarly, Nygård et al (2013) found a connection between humidity and temperature inversion strength, as well as between humidity and temperature inversion depth, in the coastal Antarctic. On the other hand, the base height of humidity inversions has been reported to be generally higher compared to the base height of temperature inversions in polar regions Nygård et al, 2013).…”
Section: Introductionmentioning
confidence: 74%
See 3 more Smart Citations
“…Devasthale et al (2011) found a clear nonlinear relationship between humidity and temperature inversion strength in all seasons except during summer in the Arctic. Similarly, Nygård et al (2013) found a connection between humidity and temperature inversion strength, as well as between humidity and temperature inversion depth, in the coastal Antarctic. On the other hand, the base height of humidity inversions has been reported to be generally higher compared to the base height of temperature inversions in polar regions Nygård et al, 2013).…”
Section: Introductionmentioning
confidence: 74%
“…The amount of water vapour typically decreases with height, but in polar regions, layers with the amount of water vapour increasing with height have been found to be very common and simultaneously occur on multiple levels (Devasthale et al, 2011;Vihma et al, 2011;Kilpeläinen et al, 2012;Nygård et al, 2013). These humidity inversions have many important implications for cloud growth and persistence in the Arctic.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…2.2.2) and corresponds to a mean value of 1 pmol mol -1 . Note that, although the definition of the height of the boundary layer over ice and snow surfaces (e.g., Anderson and Neff, 2008) is out of the scope of this work, the BrO detection limit here provided may be regarded as an upper limit of BrO in the free troposphere since former studies place the top of the boundary layer in Antarctica between 100 m and 2 km, depending on the boundary layer parametrization and time of the year (e.g., King et al , 2006;Nygård et al, 2013). This upper limit of BrO in the free 5 troposphere of Antarctica is consistent with the few previous studies of the vertical distribution of this trace gas in the Arctic and Antarctic regions that set upper limits of BrO in the polar free troposphere of 1.5 and 2 pmol mol -1 , respectively (e.g., Frieß et al, 2011;Prados-Roman et al, 2011;Peterson et al, 2017;Hüneke et al, 2017).…”
Section: Vertical Profiles Of Bro In the Antarctic Tropospherementioning
confidence: 97%